Evaluation of the effect of a resorbable membrane on the closure of palatal fistulas - Wang, Yufeng; Yang, Fangling; Liu, Weilong; Fan, Xiaofen; Lu, Yong (Frontiers in Surgery, 2023)
Purpose: Palatal fistula following closure of palatal clefts remains a difficult clinical complication. Surgical treatment of fistulas is often complicated with high recurrence rates. We present our results of fistula closure augmented with GTR, a resorbable membrane designed to promote guided tissue regeneration. Methods: We reviewed the records of 75 patients operated between 2008 and 2022 for closure of palatal fistula. The patients comprised 24 who underwent fistula closure augmented with GTR and 51 with other techniques. We reviewed the age at surgery, sex, location of fistula and outcome. Operation success was defined as an asymptomatic patient along with a healed fistula on clinical examination. Results: The overall fistula closure rate was 79.1% in GTR group and 76.5% in the non-GTR group, respectively (P=0.79). Discussion: The success rate of fistula closure in GTR group is comparable with the non-GTR group in this study. An additional advantage is that this procedure does not require harvesting of any autologous tissue and reduce the tissue damage in the long term.